“Овесець”: до семантики мотиву традиційноїорнаментики гончарних виробів Лівобережної України - Рахно, К. (Народна творчість та етнографія, 2005)
Several traditional family observances, such as birth, wedding, funeral, are under a detailed study in this article. A symble that is present in all of them - the oat - is interpreted. The author claims that it is relevant to a similar symble in traditional pottery - "Ovesets" - a model of pagan universe. The importance of the sign is proved through a number of explanations of the functioning of the symble of oat. The research of different versions of the symble helps comprehend the archaic outlook; it provides understanding of attitude towards death and life cycles in a traditional society.